ANALYSIS OF STUDENTS' MATHEMATICAL PROBLEM SOLVING ABILITY BASED ON POLYA'S PROCEDURE ON THE SYSTEM OF LINEAR EQUATIONS WITH TWO VARIABLES - Indirawati, Dita; Muslimahayati, Muslimahayati; Sunarto, Sunarto (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2024)
This study aims to analyze the mathematical problem solving ability of eighth grade students at MTs al-Munawarah using the Polya procedure on the material of two-variable linear equation systems. Data collected through problem solving ability tests and interviews. Indicators of problem solving ability based on Polya include; understanding the problem, planning problem solving, implementing the solution and rechecking. This research method uses a descriptive qualitative approach. The data analysis used is descriptive statistics. The results of the analysis show that subjects with high ability are able to fulfill the Polya procedure indicators well and show significant improvement. Furthermore, subjects with moderate ability are only able to fulfill three indicators in the Polya procedure, namely the fourth indicator is rechecking the subject does not recheck the answers that have been completed. While low ability subjects can only fulfill one indicator, namely the subject is able to understand the problem in the question, but low ability subjects still have difficulty in compiling and implementing problem solving and do not recheck the answers.